Geographic Information Systems of Small Industry Development During Pandemic - Andrian Sah; Sukma Dwi Prakoso; Mursalim Tonggiroh (Universitas Islam Kuantan Singingi, 2021)
During the pandemic it caused disruption in all fields, including Small Industries. One of them is small Industries in the city of Jayapura experienced taking down of sales during the pandemi. Industry fields gave helping for small industry in Jayapura as improvement and stability to improve Small Industries during this pandemic. The Department of Industry, Trade, Cooperatives and SMEs only has information data from Small Industry Assistance and there is no development data, especially during the pandemic, development level data is needed to view and store data from observations. Therefore it is necessary to have a geographic information system to collect and provide information to small industries regarding the level of development, using the PIECES analysis method, designing using the Unified Modeling Language (UML) method, using the waterfall development method and the software used is QGIS. This research produced a Geographic Information System for the Development of Small Industries in the Pandemic as information for small industries in North Jayapura.